2013
DOI: 10.1051/parasite/2013044
|View full text |Cite
|
Sign up to set email alerts
|

Is reactivation of toxoplasmic retinochoroiditis associated to increased annual rainfall?

Abstract: Background: Reactivation of toxoplasmic retinochoroiditis is the most frequent form of uveitis in Misiones, Argentina. Fluctuations in the number of patients consulting with this type of uveitis were detected during the last decade. Since the province was consecutively exposed to rainy and dry periods over the last years, we decided to explore whether a relationship between reactivation of toxoplasmic retinochoroiditis and rain might be established according to the data registered during the 2004–2010 period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The relationship between rainfall and toxoplasmosis has become a particularly relevant topic, as a Colombian multicentric study found a statistically significant association between congenital toxoplasmosis seropositivity and the mean annual rainfall (Gómez-Marin et al, 2011). Additionally, pluviosity has been related to an increase in the frequency of toxoplasmic reactivation episodes in humans (Rudzinski et al, 2013) and the risk of seroconversion for Tg in cats (Afonso et al, 2010). However, with our data is not possible to establish the relationship between rainfall and toxoplasmosis.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The relationship between rainfall and toxoplasmosis has become a particularly relevant topic, as a Colombian multicentric study found a statistically significant association between congenital toxoplasmosis seropositivity and the mean annual rainfall (Gómez-Marin et al, 2011). Additionally, pluviosity has been related to an increase in the frequency of toxoplasmic reactivation episodes in humans (Rudzinski et al, 2013) and the risk of seroconversion for Tg in cats (Afonso et al, 2010). However, with our data is not possible to establish the relationship between rainfall and toxoplasmosis.…”
Section: Discussionmentioning
confidence: 69%
“…Regarding geographical variation, one Colombian study found an association between the high prevalence of congenital toxoplasmosis and pluviosity (Gómez-Marin et al, 2011). Another study found an association between pluviosity and toxoplasmosis reactivation (Rudzinski et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding congenital infection, Go ´mez-Marin's et al study [10] found a statistically PLOS NEGLECTED TROPICAL DISEASES significant association between annual rainfall and congenital toxoplasmosis. With respect to OT relapses, a study carried out in Argentina found that the frequency of toxoplasmic reactivation episodes increases when precipitation increases and that the mean annual rainfall could be a predictor of the frequency of reactivations; for every mm of rainfall, there was a 2% increase in the reactivation episodes (OR = 1.002, 95% CI = 1.000-1.003, P = 0.019) [11].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the mean annual rainfall significantly correlates with the incidence of congenital toxoplasmosis [ 10 ]. Furthermore, another study found a positive correlation between the annual precipitation and toxoplasmic retinochoroiditis reactivation rate [ 11 ]. This correlation could exist because oocyst survival is higher in humid, warm soil than under dry conditions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation